BULK VISCOUS COSMOLOGICAL MODELS WITH LINEARLY VARYING DECELERATION PARAMETER IN A SCALE COVARIANT THEORY OF GRAVITATION - Singh, S Surendra (Journal of Global Research in Mathematical Archives(JGRMA), 2015)
Friedmann Robertson Walker universe in the presence of viscous uid are investigated in the cosmological theory based on the scale covariant theory of gravitation by considering the deceleration to be linearly variable. Exact solutions have been obtained from which cosmological models have been derived. The universe ends with big rip. Dynamical and physical implications of the solutions have been briefly studied.